2008
DOI: 10.1016/j.jmb.2008.08.070
|View full text |Cite
|
Sign up to set email alerts
|

A DExH/D-box Protein Coordinates the Two Steps of Splicing in a Group I Intron

Abstract: SummaryProteins of the DExH/D family are ATPases that can unwind duplex RNA in vitro. Individual members of this family coordinate many steps in ribonucleoprotein enzyme assembly and catalysis in vivo, but it is largely unknown how the action of these co-factors is specified and precisely timed. As a first step to address this question biochemically, we describe the development of a new proteindependent group I intron splicing system that requires such an ATPase for coordinating successive steps in splicing. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 54 publications
4
32
0
Order By: Relevance
“…2B). Notably, mrs1⌬ showed enhanced accumulation of aI5␤-containing COX1 pre-mRNA, which is consistent with the Mrs1p protein having a role in the first step of splicing (27). Protein cofactors having a role after the first step of splicing, such as Pet54p, are likely to have loss of ligated exon product, with no increase in the amount of pre-mRNA because the partially spliced product is likely to be unstable (28).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…2B). Notably, mrs1⌬ showed enhanced accumulation of aI5␤-containing COX1 pre-mRNA, which is consistent with the Mrs1p protein having a role in the first step of splicing (27). Protein cofactors having a role after the first step of splicing, such as Pet54p, are likely to have loss of ligated exon product, with no increase in the amount of pre-mRNA because the partially spliced product is likely to be unstable (28).…”
Section: Resultssupporting
confidence: 66%
“…Question marks reflect a gap in our knowledge of the degree to which Suv3p recycles Mrs1p from aI5␤ versus bI3. (27,37,49). The affinity is modest, but as shown for the bI3 intron, other splicing cofactors can increase affinity of Mrs1p for its RNA targets (49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an in vitro study on splicing of the aI5␤ intron, Mrs1 was found to promote the first step in splicing, whereas Mss116 acts subsequently in the exon ligation reaction (47). Because Mrs1 functions at an early step in aI5␤ splicing, we sought to assess the functional relationship of Mrs1 and Mne1.…”
Section: Mne1mentioning
confidence: 99%